Makna Kopi Bagi Masyarakat Gayo - ABYATAR, ABYATAR ([Yogyakarta] : Universitas Gadjah Mada, 2014)
The study of meaning from the standpoint of coffee producer communities not been much studied, so it is worth to do indepth studies for this issue. This study reveal the meaning of coffee for the people of Gayo who have a different viewpoints and perceptions because of specific consumption and production processes. The purpose and objective assessment of this study is to find out and reveal the meaning of coffee in different arena and habitus. Using the power of the phenomenological method in tracking and comparing the interpoint of view, the perception will be visible and deep meanings are drawn. To see the perception of the meaning of coffe for Gayo people, this study will use Edward Said's theory of Bourdieu as a collaboration. Bourdie theory used to form the frame of the diversity of perception through the realm of concepts and habitus; Said theory while considering the perception of post-colonial hegemony and identity of eastern. Both of them are bridged by the other concept of Bourdieu which is; taste. In the perceptual search revealed a variety of coffee meaning for the Gayo people in three different domains. First, the meaning of coffee is based by the knowledge and hegemony of colonial interests. This is illustrated by the people who appear on the “warung kopi saring”. But, secondly, it is slowly changing by knowledge through a new space for coffee consumption like café which flourishing 2 years ago. Tastes began to be discussed which means indirectly discussing discourse and hegemony. Consequently, third, appeared \"coffee lovers\" and \"coffee drinkers\". Various backgrounds such as job, generation, and gender identity and began dealing in the arena separate classification arising from the discussion tastes. When the arena of meaning find its pattern, there is another side which affect the breadth of meaning. Everyday experiences and perceptions limiting and expanding on the same time the meaning of coffee. Meaning in the arena of coffee can be discussed as welfare, the role of government, to the technical intricacies cause sentiment among the players in the coffee production chain. In the epilogue then drawn that which time ago; taste hegemonized, now twisted into a weapon in a “post-colonial project”. When tastes are constructed and then discussed, the reconstruction is in progress. Arena as well as the different habitus gives different meanings. Gayo people who not only see it from the arena of consumption and not only talk about taste, but also see it from their mode of production and income. Keyword: meaning, coffee, Gayo, taste, orientalism, habitus, arena